2021
DOI: 10.1038/s41598-021-03174-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolic syndrome and risk of psoriasis: a nationwide population-based study

Abstract: Metabolic syndrome (MetS) is associated with psoriasis, but it remains unclear whether risk of psoriasis remains in patients whose MetS diagnosis changes. To assess the relationship between risk of psoriasis and changes in MetS components. We obtained data from the National Health Insurance Service of Korea and divided the participants into four groups: individuals without MetS (control); individuals with MetS in 2009, but without MetS in 2012 (pre-MetS); individuals without MetS in 2009, but with newly diagno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Although the exact causal relationship between IR and psoriasis has not been fully established, observational studies have shown that waist circumference has the strongest association with psoriasis, followed by high-density lipoprotein and triglyceride levels. Additionally, patients with persistent metabolic syndrome have a higher risk of developing psoriasis ( 33 ). Our own study supports these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact causal relationship between IR and psoriasis has not been fully established, observational studies have shown that waist circumference has the strongest association with psoriasis, followed by high-density lipoprotein and triglyceride levels. Additionally, patients with persistent metabolic syndrome have a higher risk of developing psoriasis ( 33 ). Our own study supports these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis patients are typically dyslipidemic [26]. Recent studies have reported that psoriasis decreases cholesterol efflux capacity as well as HDL composition [6,27,28]. A previous study reported that HDL's antioxidant and anti-inflammatory effects decreased in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Patient:innen mit einer Psoriasis haben in Abhängigkeit von Erkrankungsschwere und -dauer ein erhöhtes Risiko, ein metabolisches Syndrom als Komorbidität zu entwickeln [ 6 , 47 ]. Umgekehrt stellt das metabolische Syndrom einen Risikofaktor für das Auftreten einer Psoriasis dar [ 29 , 37 ]. Als Diagnosekriterien für ein metabolisches Syndrom gelten der Bauchumfang bei Männern von mehr als 94 cm und bei Frauen von mehr als 80 cm sowie das Vorliegen von mindestens 2 weiteren der folgenden Störungen: arterielle Hypertonie (systolisch ≥ 130 mm Hg, diastolisch ≥ 85 mm Hg als Mittelwert einer 24-h-Langzeitblutdruckmessung oder alternativ systolisch ≥ 140 mm Hg, diastolisch ≥ 90 mm Hg als wiederholte Einzelmessung) oder eine bereits behandelte arterielle Hypertonie, Nüchtern-Triglyzeride ≥ 150 mg/dl (≥ 1,7 mmol/l) (ohne Medikation), HDL-Cholesterin < 40 mg/dl (< 1,03 mmol/l) bei Männern und < 50 mg/dl (< 1,29 mmol/l) bei Frauen, erhöhte Nüchtern-Blutglukose ≥ 100 mg/dl (≥ 5,6 mmol/l) bzw.…”
Section: Metabolisches Syndromunclassified